A Study of Leadership Behavior and Its Implications for Organizational Culture at PT PLN (Persero) - Amir; Angriawan; Khaeriyah, Hidayatul; Nurfadillah (Indonesian Journal of Social Science Research, 2024)
The leadership behavior at PT PLN (Persero) has significant implications for the formation, development, and change of the organizational culture within the company. When leaders demonstrate behaviors that promote values such as integrity, collaboration, and innovation, this can positively influence the organizational culture. The objective of this research is to explore how leadership behavior at PT PLN (Persero) affects the formation and development of the organizational culture within the company. The method used in this research is a systematic literature review. The findings of this research indicate that all patterns of leadership behavior at PT PLN have a significant impact on the motivation, commitment, and performance of employees towards the company's goals and values. Inspirational and empowering leadership fosters an organizational culture based on loyalty and dedication.